O discurso do mestre-de-cerimônias: perspectiva dialógica - Silva, Renata Almeida de Souza Aranha e (2007)
The focus of this paper is to present an analysis of the speech given by a Master-of-Ceremonies, an activity carried out by professionals from various backgrounds, whose purpose is to conduct public, social or institutional events. Results of the analysis of selected data will be presented from two main points. On one side, the performance of the master-of-ceremonies in two Rector Investiture Ceremonies, that occured in two colleges located in São Paulo. These performances were captured through video-tapes of the ceremonies and also through scripts specially prepared for both occasions. On the other side - also a pivotal part in the analysis of the activity of the master-of-ceremonies - the rules that guide the performance of this professional, collected in specific manuals, and the laws that regulate the ceremonial in Brazil. Based on the concepts of concrete statement, verbal interaction and discursive genre, from the theory of M. Bakhtin and his circle, the data used for the analysis focuses on verbal communication associated to an extra verbal situation at the events, considering each ceremony to be a concrete statement. The event of PUC São Paulo's rector, in 2004, was conducted by a professor who's been with the College for 30 years and has established a relationship with the institution that enabled the confrontation of the individual style and the generic, without breaking up with the genre. Even without rules set down for his performance, a detailed script, PUC's master-of-ceremonies was directed by a professor that was positioned at a strategical place in the audience. At USP's event, a master-of-ceremonies was hired to conduct the event and didn't have the same room to create his lines, although the rigid script didn't annul the individual stylistic composition. In both situations we verify that the elements that distinguish the speech of the master-of-ceremonies constitute a discursive genre, and that the unpredictable is one of the elements that integrate this genre